Video Kabupaten Tangerang Pada Dinas DISPORABUDPAR Pariwisata - Azwar Aditya Putra; Vella Carisa (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2019)
Video information designed this explains the diversity and wealth of attractions that exist in the current, so it can be an attraction for both local and foreign tourists as well as the public, to know there is tourist information in Tangerang Regency. The purpose of this research is to achieve the target of Disporabudpar in terms of conveying information about the sights of the Tangerang Regency to the community and tourists, as well as increase the number of tourists visit every year. As for the research methods used in this study include Data collection, analysis of the design of the Media, and the concept of Media Production (KPM) which include: pre production, production, and post production. Tourist information through the medium of Tangerang Regency designed will be informed via the Youtube Website: Tangerang Regency, Disporabudpar Website and facebook. The expected target of Disporabudpar i.e., tourists and the public can know the diversity existing tourist attractions in Tangerang Regency, and can increase the number of tourists visiting the Tangerang Regency each year.